Invasive Vaucheria (Xanthophyceae) at the lower shore of the Wadden Sea. Issue 3 (4th May 2022) - Rybalka, Nataliya; Epkes, Simon; Wegner, K. Mathias; Michaelis, Rune; Reise, Karsten
ABSTRACT: Vaucheria species have previously been restricted to upper shore habitats in the Wadden Sea (eastern North Sea, European Atlantic). In contrast to these previous observations, we have now found Vaucheria longicaulis and a distinct plastid lineage of V. velutina spreading along the lower shores, forming extensive turfs at and below low tide level under fully marine conditions near the Island of Sylt. Species and populations were identified by morphological features and reconfirmed by sequencing the plastid-encoding gene rbc L and the psb A- rbc L spacer region. We needed to modify primer sequences to successfully amplify the rbc L region of marine and brackish Vaucheria species. Due to distinct phylogenetic grouping, we can reject the possibility of niche expansions from the upper shore and propose recent introductions as the cause of the newly formed populations at the lower shore.